2010
DOI: 10.2134/agronj2009.0142
|View full text |Cite
|
Sign up to set email alerts
|

A Risk Analysis of Converting Conservation Reserve Program Acres to a Wheat–Sorghum–Fallow Rotation

Abstract: This study examines the economic potential of producing a wheat (Triticum aesitivum) and grain sorghum (Sorghum bicolor (L.) Moench) rotation with three different tillage strategies (conventional, reduced, and no tillage) compared with the Conservation Reserve Program (CRP) in a semiarid region. This research uses enterprise budgeting and stochastic efficiency with respect to a function to determine the preferred management strategies under various risk preferences. Yields, input rates, and field operations fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Higher N application increased NR risk and high N was not the preferred option for risk-averse producers (Pendell et al, 2007;Meyer-Aurich et al, 2009). Converting Conservation Reserve Program land back into annual crop production was found to be more risky than remaining in the program, but with high grain prices, risk-neutral or slightly risk-averse producers would prefer annual cropping if using reduced tillage or no-till (Williams et al, 2010). An analysis of malting barley production risk, including yield, price, and acceptance risk, found that the insurance and contracting strategy infl uenced risk premiums and the preferred strategy (Wilson et al, 2009).…”
mentioning
confidence: 99%
“…Higher N application increased NR risk and high N was not the preferred option for risk-averse producers (Pendell et al, 2007;Meyer-Aurich et al, 2009). Converting Conservation Reserve Program land back into annual crop production was found to be more risky than remaining in the program, but with high grain prices, risk-neutral or slightly risk-averse producers would prefer annual cropping if using reduced tillage or no-till (Williams et al, 2010). An analysis of malting barley production risk, including yield, price, and acceptance risk, found that the insurance and contracting strategy infl uenced risk premiums and the preferred strategy (Wilson et al, 2009).…”
mentioning
confidence: 99%
“…Furthermore, Klemme [3] stated that changes in yields or costs, such as reduced herbicide costs through improved weed control in no-till planting, could lead to quite different tillage system rankings for risk averse farmers (and consequently improve the relative attractiveness of no-till). This observation was confirmed by Williams et al [25] who noted that in the current economic environment the volatility of input costs may play nearly as big a role in tillage and cropping decisions as commodity prices.…”
Section: Discussionmentioning
confidence: 54%
“…They concluded that, although deficit irrigation was stochastically more efficient than full irrigation under limited water supply conditions, irrigation farmers would not voluntarily choose to conserve water through deficit irrigation and would require compensation to do so. Finally, Williams et al [25] examined the economic potential of producing a wheat and grain sorghum rotation with three different tillage strategies (conventional, reduced, and no-till) compared with the Conservation Reserve Program (CRP) in a semiarid region. They used enterprise budgeting and SERF to determine the preferred management strategies under various risk preferences.…”
Section: Introductionmentioning
confidence: 99%
“…This modelling approach is a common risk analysis method for economic analyses and has been applied to, for example, organic production systems, tillage, and N rates (Lien et al 2007;Meyer-Aurich et al 2009;Williams et al 2010). An analysis of malting barley production risk, including yield, price, N rate, and type of barley, found risk-averse producers would reduce their risk by growing feed barley rather than malting and by reducing N fertility .…”
Section: Introductionmentioning
confidence: 99%